COSTA RICA Y EL TRATADO DE LIBRE COMERCIO CON LOS ESTADOS UNIDOS - Jiménez Gómez, Roberto (Universidad de Costa Rica, 2023)
During the negociation of CAFTA, Costa Rica made concessions of great economic, social and environmental impact in areas such as generic drugs, agriculture, and deregulation of telecomunications and insurance. The scope of CAFTA and the concessions may modify Costa Rica’s development model, by restricting the aplicability of public policy promoting the productive sectors which in turn may limit development opportunities. Social participation and national interest should guide and are paramount to the negociation and ratification of CAFTA, were it determined to be the most appropriate development path.